THE CORRELATION BETWEEN THE STUDENTS' INTEREST IN READING POETRY AND THEIR ABILITY TO ANALYZE POETRY AT SMA KARTIKA I-2 MEDAN - Hepnyi Samosir; Merry Susanty Tarigan; Erika Kartika Mastiur Manalu (STKIP Siliwangi, 2018)
This study is a correlational design with the aim of finding out if there is any positive correlation between the students’ interest in reading poetry and their ability to analyze poetry at SMA Kartika I-2 Medan. The study was conducted at SMA Kartika I-2 Medan. The product moment correlation formula was used to determine the correlation between the students’ interest in reading poetry and their ability to analyze poetry. The hypothesis was tested by comparing the value of rcount to rtable on the degree of freedom (df) = 30 - 2 = 28 with α = 0.05 significance level and df = 28 (0.361). It was found that rcount was higher than rtable (0.726> 0.361), and thus null hypothesis was successfully rejected. The result of the study shows that there was any positive correlation between the students’ interest in reading poetry and students’ ability to analyze poetry at the eleventh grade students of SMA Kartika I – 2 Medan. The correlation coefficient was 0.726, and the regression line was Y = 12.07 + 0,948x. The contribution of the students’ interest in reading poetry to their ability to analyze poetry is 47.29%. Keywords: Ability, Analyze, Correlation, Interest, Poetry